Converging Pathways in Autism Spectrum Disorders: Interplay between Synaptic Dysfunction and Immune Responses - Voineagu, Irina; Eapen, Valsamma (Frontiers in Human Neuroscience, 2013)
Autism spectrum disorders (ASD) are highly heritable, yet genetically heterogeneous neurodevelopmental conditions. Recent genome-wide association and gene expression studies have provided evidence supporting the notion that the large number of genetic variants associated with ASD converge toward a core set of dysregulated biological processes. Here we review recent data demonstrating the involvement of synaptic dysfunction and abnormal immune responses in ASD, and discuss the functional interplay between the two phenomena.